Plant mucilages. II. Isolation and characterization of a mucous polysaccharide, "odoratan," from Polygonatum odoratum var. japonicum rhizomes - Tomoda, M; Yoshida, Y; Tanaka, H; Uno, M (Chemical & pharmaceutical bulletin, 1971)
A mucous polysaccharide, named odoratan, has been isolated from the rhizomes of Polygonatum odoratum DRUCE var. japonicum HARA. It was homogeneous on gel chromatography and glass-fiber paper electrophoresis. The component carbohydrates of it were D-fructose, D-mannose, D-glucose and D-galacturonic acid, and the molar ratio of them was 6 : 3 : 1 : 1. 5. Component D-fructose was almost liberated by the digestion with β-fructofuranosidase.